PENGGUNAAN PARTIKEL AKHIR YO DAN NE BERDASARKAN TEORI TERITORI INFORMASI - Tri Desti Purnama Sari; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In Japanese, sentence-ending particles yo and ne appeared frequently to show the speaker's atitude. This study explains the use and meanings of the sentence-ending particles of yo and ne based on Information Territory Theory that introduce by Kamio Akio (1990). The result of this research, yo is used on information that the territory of the speaker and the territory of the listener. The final particle yo is used when conveying information and requesting information. Ne is used on information that the territory of the speaker and listener. Futhermorethe, ne also used on exists in both of the speaker and listener, but only partially in territory speaker and that the listener. Ne is used when asking for confirmation and asking for certainty. In other words, information for listeners and speakers is influenced by the information territory.Key Words: Sentence Ending Particles, Information Territory Theory, Meanings